Bronchoscopic submucosal dissection with Hybrid Knife: a new technique treating tracheal leiomyoma. (7th February 2021) - Gu, Chuanjia; Chen, Junxiang; Zheng, Xiaoxuan; Sun, Jiayuan
Abstract: Primary tracheal leiomyoma is exceedingly rare and recommended management has not been defined yet. Surgical management has been considered to be the standard treatment historically. Bronchoscopic intervention may be an ideal alternative for patients who refuse or are not fit for surgery. We report the first bronchoscopic submucosal dissection using an innovative water-jet Hybrid Knife performed on a patient with recurrent primary tracheal leiomyoma.